2020
DOI: 10.36706/jisd.v7i2.13255
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Hasil Belajar Daring Peserta Didik Selama Pandemi Covid-19 Melalui Pemanfaatan Fitur Aplikasi Zoom Di Sd Negeri 77 Palembang

Abstract: This Classroom Action Study was aimed at describing the online learning outcomes improvement and learning process of Grade VI students in Public Elementary School 77 Palembang through the using of Zoom Aplication. The research was conducted through two cycles of action. The diagram shows that the exhaustiveness increased from cycle I at 47% to 88% after cycle II. The learning outcomes also improved from cycle I to II at 63.8 and 82.9 respectively. This study concluded that through the using of Zoom Application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Mastery of knowledge and skills is more effective individuals experience it themselves not only waiting for material from the facilitator but must make their own efforts to find new knowledge and skills and then integrate them with knowledge and skills that they already have before (Putra & Nisaurrasyidah, 2020) Other research also revealed Monica & Fitriawati (Monica & Fitriawati, 2020) online learning received very good responses from students because learning is more flexible when using it. Gunawan's research (Gunawan, 2020) added that online learning using the zoom application and WhatsApp Group improves online learning outcomes in thematic learning. Online learning can also have the advantage of fostering learning independence and increasing learning motivation and courage to express opinions (Sadikin & Hamidah, 2020) Based on the results of this study, the results of the implementation of the toddler mother class both using WhatsApp Group media and through conventional / face-to-face methods were both effective in increasing the knowledge of toddler mothers, but based on the average results of the implementation of the toddler mother class using Satryani, Nina Mardiana, Gajali Rahman/KESANS Effectiveness of use Whatsapp Groups in Implementation of Classes for Mothers Toddlers Aged 0-1 Years Against Knowledge of Mothers Toddlers in the Technical Implementation Unit, Barong Tongkok Community Health Center in 2022 conventional methods has a higher average increase in knowledge, this is due to the implementation of the Toddler Mother Class using WhatsApp Group media There is a shortcoming that the facilitator cannot monitor the development of the respondent directly or the facilitator is difficult to measure the character of the respondent because to measure the character must be by interacting and analyzing directly.…”
Section: Discussionmentioning
confidence: 99%
“…Mastery of knowledge and skills is more effective individuals experience it themselves not only waiting for material from the facilitator but must make their own efforts to find new knowledge and skills and then integrate them with knowledge and skills that they already have before (Putra & Nisaurrasyidah, 2020) Other research also revealed Monica & Fitriawati (Monica & Fitriawati, 2020) online learning received very good responses from students because learning is more flexible when using it. Gunawan's research (Gunawan, 2020) added that online learning using the zoom application and WhatsApp Group improves online learning outcomes in thematic learning. Online learning can also have the advantage of fostering learning independence and increasing learning motivation and courage to express opinions (Sadikin & Hamidah, 2020) Based on the results of this study, the results of the implementation of the toddler mother class both using WhatsApp Group media and through conventional / face-to-face methods were both effective in increasing the knowledge of toddler mothers, but based on the average results of the implementation of the toddler mother class using Satryani, Nina Mardiana, Gajali Rahman/KESANS Effectiveness of use Whatsapp Groups in Implementation of Classes for Mothers Toddlers Aged 0-1 Years Against Knowledge of Mothers Toddlers in the Technical Implementation Unit, Barong Tongkok Community Health Center in 2022 conventional methods has a higher average increase in knowledge, this is due to the implementation of the Toddler Mother Class using WhatsApp Group media There is a shortcoming that the facilitator cannot monitor the development of the respondent directly or the facilitator is difficult to measure the character of the respondent because to measure the character must be by interacting and analyzing directly.…”
Section: Discussionmentioning
confidence: 99%
“…Dengan berinteraksi tersebut dapat meningkatkan hasil belajar IPS siswa. Sejalan dengan penelitian yang dilakukan oleh indra gunawan (Gunawan, 2020) bahwa pembelajaran daring dengan menggunakan aplikasi zoom dapat meningkatkan hasil belajar di SD.…”
Section: Terdapat Perbedaan Hasil Belajar Ips Dengan Menggunakan Pemb...unclassified